19th IEEE International Parallel and Distributed Processing Symposium
DOI: 10.1109/ipdps.2005.363
|View full text |Cite
|
Sign up to set email alerts
|

Production Scheduling by Reachability Analysis - A Case Study

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Many specialized exact algorithms and heuristics have been developed to deal with o ine and online optimization of job shop and ow shop variants. A plethora of optimization objectives have been de ned [10], among which are minimizing makespan [1,6,13,15], total tardiness [11], maximum lateness [7] mean ow time [14], and total completion time [5,12]. Some approaches can deal only with processing times, others include set-up times, or due dates.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many specialized exact algorithms and heuristics have been developed to deal with o ine and online optimization of job shop and ow shop variants. A plethora of optimization objectives have been de ned [10], among which are minimizing makespan [1,6,13,15], total tardiness [11], maximum lateness [7] mean ow time [14], and total completion time [5,12]. Some approaches can deal only with processing times, others include set-up times, or due dates.…”
Section: Related Workmentioning
confidence: 99%
“…Some approaches can deal only with processing times, others include set-up times, or due dates. Other approaches deal with claiming (multiple) shared resources and simultaneously solve a mapping problem and a sequencing problem [1]. Use cases such as production lines for mirrors, lacquer [1] and textile [13] have been researched.…”
Section: Related Workmentioning
confidence: 99%
“…an optimal schedule. However, it was shown that this technique, extended by suitable heuristics, allows to find good schedules in very short time [5,6].…”
Section: Uppaal and Uppaal Coramentioning
confidence: 99%
“…In earlier work [5,6] we experimented with several heuristics. In the current context, we used only greediness as strategy and restrict the number of orders that may be processed at any point in time.…”
Section: Uppaal Modelsmentioning
confidence: 99%
See 1 more Smart Citation